Strategic gaze: an interactive eye-tracking study - J. Hausfeld; K. von Hesler; S. Goldlücke (Experimental Economics, 2020)
We present an interactive eye-tracking study that explores the strategic use of gaze. We analyze gaze behavior in an experiment with four simple games. The game can either be a competitive (hide & seek) game in which players want to be unpredictable, or a game of common interest in which players want to be predictable. Gaze is transmitted either in real time to another subject, or it is not transmitted and therefore non-strategic. We find that subjects are able to interpret non-strategic gaze, obtaining substantially higher payoffs than subjects who do not see gaze. If gaze is transmitted in real time, gaze becomes more informative in the common interest games and players predominantly succeed to coordinate on efficient outcomes. In contrast, gaze becomes less informative in the competitive game.
Keywords: C91; D01; D83; D87; C72; 330; Eye-tracking; Focal points; Signaling; Hide & seek